Incidence and risk factors of immune reconstitution inflammatory syndrome in HIV-TB coinfected patients - Dibyendu,De (2011)
Tuberculosis is one of the leading causes of development of Immune reconstitution inflammatory syndrome (IRIS) in HIV patients receiving antiretroviral therapy (ART). OBJECTIVE: To determine the incidence of IRIS in HIV-TB coinfected patients, and to find out the possible risk factors associated with IRIS. MATERIALS AND METHODS: Study commenced with 96 patients adhered to standard antitubercular therapy (ATT) and ART without defaultering, and followed up for six months. RESULT: The mean (± SD) CD4 count and CD4 percentage at baseline was 59.16 (± 24.63) per mm³ and 4.59% (± 1.73) respectively. Only 18.75% developed IRIS after 57.05 (± 14.12) days of initiation of ART. Extrapulmonary tuberculosis was the most significant factor associated with IRIS (83.33%) than those without IRIS (44.87%) (p = 0.0032). Specifically, tubercular lymphadenitis (38.88%, p = 0.0364) and disseminated tuberculosis (33.33%, p = 0.0217) were significantly associated with IRIS. The other risk factors associated with appearance of IRIS were higher CD4 count (p = 0.0212) at three months after initiation of ART and increment of CD4 count (p = 0.0063) and CD4 percentage (p = 0.0016) during this period. The major manifestations of IRIS were fever (40%), followed by lymphadenitis (38%). The mortality rate in IRIS was not higher than those without IRIS. CONCLUSION: Patients with extrapulmonary tuberculosis, especially tubercular lymphadenitis, were more likely to develop IRIS and fever was associated in most of them. Higher increment of CD4 count may indicate development of IRIS in presence of new or worsening tuberculosis lesion.